INTEGRATION OF EDUCATION IN DIFFERENT COUNTRIES OF THE WORLD AND PROBLEMS OF VOCATIONAL TRAINING FOR YOUNG PEOPLE (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This study analyzes the effectiveness of the education system, young people’s vocational preparation, and their adaptation to the labor market based on the experience of developed countries. The study examines dual and modular systems, technological approaches, and individual educational strategies used in countries such as Germany, Japan, the United States, and Finland. It also identifies major problems such as the mismatch between education and the labor market, technological changes, insufficient funding, regional inequality, and the shortage of qualified teachers. The findings of the study make it possible to determine solutions and prospects for strengthening educational integration, adapting young people to modern professions, and ensuring socio-economic stability.
Keywords: Educational integration, vocational preparation, labor market, dual education, modular system, digital skills, entrepreneurship, teacher qualification, regional inequality, social stability.